On the taxonomy of genus Gnathocinara Dierl, 1978 (Lepidoptera, Bombycidae) from India with description of a new species - Sarkar, Ankhi; Joshi, Rahul; Mollah, Kaiyum Baskh; Singh, Navneet (Zootaxa, 2025)
A new species, Gnathocinara zolotuhini sp. nov., is described from Meghalaya, India, representing the first report of this genus from the Indian subcontinent. Detailed descriptions, habitus photographs, and illustrations of the male genitalia are provided for the newly described species. Furthermore, this study addresses and clarifies potential errors in the generic characterization of Gnathocinara and in the description of G. boi Wang & Zolotuhin, 2015.